Peroxymonosulfate/base process in saline wastewater treatment: The fight between alkalinity and chloride ions. (May 2018) - Yang, Fei; Huang, Ying; Fang, Changling; Xue, Ying; Ai, Luoyan; Liu, Jianshe; Wang, Zhaohui
Abstract: Both Cl − and base can affect PMS activation to produce reactive chlorine or oxygen species, but the overall effects of chloride on this emerging PMS/base technology in saline wastewater treatment are unknown. Here effectiveness of PMS/base, PMS/Cl − and PMS/base/Cl − is compared with a gradient concentration of chloride and alkalinity, by probing the degradation of methylene blue (MB). Both PMS/base and PMS/Cl − systems can rapidly degrade MB due to the generation of singlet oxygen and reactive chlorine, respectively. Interestingly, dye degradation and adsorbable organic halides (AOX) formation are inhibited in the PMS/base/Cl − system as high concentrations of Cl − and base co-exist. Reaction of PMS with chloride diminishes the effective concentration of PMS by base activation, whereas in return high alkalinity decreases the oxidation capacity of reactive species. Therefore, this finding may have significant technical implications for evaluating the applicability of the emerging PMS/base technology and optimizing the conditions for AOX abatement in PMS-based processes. Graphical abstract: Image 1 Highlights: Negligible effects of chloride on PMS/base system at a low alkalinity are observed. Dye degradation is inhibited in PMS/base/Cl − system as Cl − /OH − are at high levels. Less AOX are formed in PMS/base/Cl − system at a high level of alkalinity.